The Digital Temptation: Adult Attachment Style and Commitment as Predictors of Online Extradyadic Involvement in Dating Partner - Shinta Saraswati; Yudiana Ratnasari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The development of social media in the digital age has increased the likelihood of Online Extradyadic Involvement (O-EDI) or online infidelity, especially among young adults who are in romantic relationships. This phenomenon is influenced by psychological factors such as adult attachment style and commitment level, which play a role in determining an individual's vulnerability to O-EDI behavior. This study aims to examine the role of adult attachment style and commitment in predicting O-EDI behavior in individuals who are in romantic relationships in Indonesia. O-EDI is defined as emotional or sexual involvement online with someone other than one's primary partner, which is done in secret. A total of 172 young adult participants aged 20–38 years (M = 24.58) participated in this study. Commitment was measured using the Investment Model Scale subscale, while adult attachment style was measured using the Experiences in Close Relationships – Short Form. Multiple linear regression analysis was performed by controlling for demographic variables. Results show that the model with three predictors explains 38.1% of the variance in O-EDI, where attachment avoidance (β=0.258, p<0.05), attachment anxiety (β=0.220, p<0.05), and commitment level (β=-0.152, p<0.05) are significant predictors. Relationship duration and education also had an effect. These findings confirm that low commitment and high insecure attachment tendencies increase the risk of O-EDI in individuals in romantic relationshipsPerkembangan media sosial di era digital meningkatkan peluang terjadinya Online Extradyadic Involvement (O-EDI) atau perselingkuhan daring, terutama di kalangan dewasa muda yang sedang menjalin hubungan pacaran. Fenomena ini dipengaruhi oleh faktor psikologis seperti adult attachment style dan tingkat komitmen, yang berperan dalam menentukan kerentanan individu terhadap perilaku O-EDI. Penelitian ini bertujuan menguji peran adult attachment style dan komitmen dalam memprediksi perilaku O-EDI pada individu yang menjalin hubungan pacaran di Indonesia. O-EDI didefinisikan sebagai keterlibatan emosional atau seksual secara daring dengan orang lain di luar pasangan utama yang dilakukan secara rahasia. Sebanyak 172 partisipan dewasa muda berusia 20–38 tahun (M = 24.58) berpartisipasi dalam penelitian ini. Komitmen diukur menggunakan subskala Investment Model Scale, sedangkan adult attachment style diukur dengan Experiences in Close Relationships – Short Form. Analisis regresi linear berganda dilakukan dengan mengontrol variabel demografis. Hasil menunjukkan model dengan tiga prediktor menjelaskan 38,1% variansi O-EDI, di mana attachment avoidance (β=0.258, p<0.05), attachment anxiety (β=0.220, p<0.05), dan tingkat komitmen (β=-0.152, p<0.05) menjadi prediktor signifikan. Durasi hubungan dan pendidikan juga berpengaruh. Temuan ini menegaskan bahwa rendahnya komitmen dan tingginya kecenderungan insecure attachment meningkatkan risiko O-EDI pada individu dalam hubungan pacaran